Plant growth-promoting genes can switch to be virulence factors via horizontal gene transfer - Stritzler, Margarita (2018)
There are increasing evidences that horizontal gene transfer (HGT) is a critical mechanism of bacterial evolution, while its complete impact remains unclear. A main constraint of HGT effects on microbial evolution seems to be the conservation of the function of the horizontally transferred genes. From this perspective, inflexible nomenclature and functionality criteria have been established for some mobile genetic elements such as pathogenic and symbiotic islands. Adhesion is a universal prerequisite for both beneficial and pathogenic plant-microbe interactions, and thus, adhesion systems (e.g., the Lap cluster) are candidates to have a dual function depending on the genomic background. In this study, we showed that the virulent factor Lap of the phytopathogen Erwinia carotovora SCRI1043, which is located within a genomic island, was acquired by HGT and probably derived from Pseudomonas. The transformation of the phytopathogen Erwinia pyrifoliae Ep1/96 with the beneficial factor Lap from the plant growth-promoting bacterium Pseudomonas fluorescens Pf-5 significantly increased its natural virulence, experimentally recapitulating the beneficial-to-virulence functional switch of the Lap cluster via HGT. To our knowledge, this is the first report of a functional switch of an individual gene or a cluster of genes mediated by HGT.